DEGRADASI LIMBAH PERTANIAN (KACANG PANJANG, CABAI, JAHE, KUNYIT, DAN LENGKUAS) DENGAN ENZIM SELULASE - , KHARISMA JELITA, Dr. Ria Millati, ST. MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Increasing concern about pollution that occurs from post-harvest biomass agricultural losses, which itâsaccumulation may lead to severe environment problems, has stimulated the interest in converting waste material into more valuable products. Those waste are some of lignocellulosic biomass that are composed of cellulose, hemicellulose, and lignin. High cellulose content can be utilized to produce simple sugar such as glucose that can be used for ethanol production. In this research, cellulose content of leaf and stem of yardlong bean and chili, and also stalk of ginger, turmerric, and galangal as post-harvest waste determined using Chesson Datta method, thenthey were hydrolized using commercial cellulase (Celluclast 1.5). After 72 hours incubation for enzymatic hydrolisis, glucose content was measured using DNS method. Results showed that cellulose content from post-harvest waste of yardlong bean, chili, ginger, turmerric, and galangal ranged between 21.23% - 29.8% and maximum glucose content ranged between 0.75 â 2.21 mg/ml. The highest content of cellulose and maximum glucose content were obtained from yardlong bean waste. Ethanol produced from glucose hydrolisis product ranged between 19.3 â 100,8 g ethanol/kg dry sample. Keywords: Agriculture post-harvest waste, cellulose, enzymatic hydrolisis, glucose, and ethanol